Bureaucracy in a Democratic State - K E N N E T H J . M E I E R , L A U R E N C E J . O â€™ T O O L E J R . (The Johns Hopkins University Press, 2006)
Can the imperatives of an administrative system be reconciled with the norms of democratic governance? Or is bureaucracy, with its expertise, insulation, and byzantine procedures, the enemy of popular control? These questions have been raised wherever administrative institutions have been a key element in a broader pattern of purportedly democratic rule. Deep suspicions have typically been aroused in situations in which anonymous bureaucrats and their managers make decisions that affect the outputs and outcomes of public policy. Bureaucrats themselves, on the other hand, have been known to treat political overseers with some suspicion, if not outright disdain and evasion. These tensions have not dissipated with the rise of more complex patterns of â€œgovernanceâ€ that encompass multiple organizations and stakeholders in networks to co-produce policy resultsâ€”a set of developments receiving particular attention recently in Western Europe and North America. Indeed, the challenges posed by such broadened notions of â€œbureaucracy,â€ loosely speaking, for democratic governance are even greater. In this book, we address these central questions by examining the results of bureaucratic and political interactions in some governance settings, to test for several of the most frequently mentioned, or feared, patterns of infl uence and to see whether bureaucratic systems weaken or strengthen the connections between public preferences and policy results. We make use of two sets of conceptual lenses: the mainstream perspective of political science on the bureaucracy-democracy nexus and the standard treatment of the subject in the research literature on public administration. Political science typically sees the democratic impulse as shaping bureaucracy, if at all, from above. The literature in this fi eld assumes the necessity for â€œpolitical controlâ€ of administrative systems by political overseers, and it tests for the health of democratic systems by seeking evidence that those at the top direct those at the bottom. Although relevant for considering the question of bureaucracy and democracy,we argue that this approach suffers from many serious limitations and does not effectively get at the nub of the issue. Public administration researchers, along with related specialists in public management and public policy, have generally ignored the political science literature on political control of the bureaucracy. This group of scholars has dismissed the political science work as quantitatively advanced but substantively trivial. Public administrationists have offered a more sophisticated perspective on how bureaucracy operates in putatively democratic systems, but they have also held to a rather sanguine view of bureaucracy in such settings. Serious students of public administration see the values held within administrative systems as aâ€”even theâ€”key element. We agree with this last point, but we are critical of the fi eld of public administration on two grounds. This research literature is short on systematic investigations of the bureaucracy-democracy link, including the issue of values, and the literature also offers manyâ€”and somewhat confl ictingâ€”injunctions as to just which values are to be embraced. This book seeks to bridge the gap between these two worlds. It challenges both perspectives by arguing that the techniques featured in the political control literature can be used in interesting ways to address questions relevant to both groups of scholars and in ways that have not previously been attempted. The book also shows that both fi elds have ignored important developments in the kinds of institutional arrangements that have almost universally been treated too simplistically in the standard notion of â€œbureaucracy.â€ The two fi elds, and audiences, are bridged in this study through a governance perspective, a thematic emphasis that focuses on the need to consider both broader, institutionally complex systems of governance and also the nitty-gritty details involved in managing the bureaucracy. The book, in short, speaks to both audiences in their native language but brings a message intended to discomfort rather than reassure. To make our arguments suitably general, we build on a general perspective regarding governance, which is introduced in the fi rst chapter and used as a reference point throughout the volume (in our own longer-term research program we used a more specifi c model of governance, which is discussed in the appendix). To make our arguments more tangible and persuasive, we include empirical analyses drawn from operating governance systems. The systems tapped for this purpose are at two levels of U.S. government: local and national. For the former, we take advantage of data drawn from hundreds of school districts in one large, diverse state; this set of empirical settings offer opportunities to explore systematically many key features of the bureaucracy-democracy question. For the latter, we tap data available in legislation and administrative rules for national policy and the institutional arrangements established to produce program results. These allow us to draw some pertinent conclusions about the shape of governance systems in recent decades. The origins of this book date to a 1973 seminar taught by Dwight Waldo on public administration and democracy; we were both students in that class. We then went our separate ways, Oâ€™Toole in public administration and Meier in political science, although we frequently addressed similar questions. In 1999 we joined forces to address a set of key empirical questions about organizations and governance. This book represents part of our broader joint research agenda, which concentrates on two persistently important themes: the public management and operation of complex governance systems designed to deliver policy results, and the intersection and mutual infl uence of politics and administration in contemporary systems of governance. As with the writing of any book, this project has caused us to incur substantial debts to others. School-district superintendents in Texas served as respondents as we sought to tap information about the management of these uniquely American forms of government. We acknowledge with gratitude the contributions of coauthors, particularly John Bohte, Thad Hall, and Sean Nicholson-Crotty, who worked with one or both of us on some of the analyses included here. PhD students at Texas A&M University and the University of Georgia, particularly those who survived a jointly taught combined seminar offered by us during fall 2002, stimulated and provoked us, with productive results for this projectâ€”and, we hope, for them. Sandy Gordon, Tom Hammond, Kim Hill, Greg Huber, David Lewis, Terry Moe, John Scholz, and B. Dan Wood offered helpful comments on the analyses in chapter 4. George Krause, LeeAnne Krause, Paul Teske, John Scholz, Dan Carpenter, and John Brehm provided comments on earlier versions of chapter 5. George Boyne, Stu Bretschneider, Amy Kneedler Donahue, Sergio Fernandez, H. George Frederickson, Holly Goerdel, Carolyn Heinrich, Patricia Ingraham, J. Edward Kellough, Laurence E. Lynn Jr., H. Brinton Milward, David Peterson, Hal G. Rainey, Bob Stein, and Richard Walker offered helpful ideas on various aspects of our research program. Diane Jones Meier and Mary Gilroy Oâ€™Toole have had to tolerate our preoccupations and distractions for a very long time; thanks to them above all.